Report on the 29th general assembly - ASEAN Inter-parliamentary organization - Asean Inter- parliamentary assembly, Hội đồng liên nghị viện ASEAN (ASEAN Inter - Parliamentary Assembly (AIPA), 2008)
Hội nghị lần thứ 29 của Tổ chức liên nghị viện ASEAN được tổ chức tại Singapore từ ngày 19-24 tháng 8 năm 2008.